Comunicación química en la boa arco iris Epicrates cenchria alvarezi (Serpentes: boidae) - Chiaraviglio de Torres, Margarita (1994)
In snakes there are two possible pheromonal sources: skin and cloacal glands. In this work, we tested both secretions in adults of Epicrates cenchria alvarezi as messages transmitters, trying to explain the role that plays this information in the social context of this species. Both secretions have shown to have pheromonal function. Conespecific odors elicited more tongue extrusions than other stimuli did. These results suggest that the snake is capable of discriminating conspecifics based on chemical cues alone.